2019
DOI: 10.3762/bjoc.15.284
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed Sonogashira coupling reactions in γ-valerolactone-based ionic liquids

Abstract: It was demonstrated that the γ-valerolactone-based ionic liquid, tetrabutylphosphonium 4-ethoxyvalerate as a partially bio-based solvent can be utilized as alternative reaction medium for copper- and auxiliary base-free Pd-catalyzed Sonogashira coupling reactions of aryl iodides and functionalized acetylenes under mild conditions. Twenty-two cross-coupling products were isolated with good to excellent yields (72–99%) and purity (>98%). These results represent an example which proves that biomass-derived safer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…Further attempts with Pd(dppf)Cl 2 and Pd 2 (dba) 3 showed no advantage in catalytic efficiency under the similar conditions (Table 1, entries 10–11). These results strongly suggested that the phosphine ligand was necessary for the successful completion of CC bond formation in the examined system consistent with a previous study 12 . Therefore, an excess amount of acetylene, mild reaction conditions (40 °C), and a catalytic amount of Pd(PPh 3 ) 2 Cl 2 were identified as the ideal reaction parameters for the successful C sp C sp2 bond formation via Cu‐free coupling reaction (Table 1, entry 3).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Further attempts with Pd(dppf)Cl 2 and Pd 2 (dba) 3 showed no advantage in catalytic efficiency under the similar conditions (Table 1, entries 10–11). These results strongly suggested that the phosphine ligand was necessary for the successful completion of CC bond formation in the examined system consistent with a previous study 12 . Therefore, an excess amount of acetylene, mild reaction conditions (40 °C), and a catalytic amount of Pd(PPh 3 ) 2 Cl 2 were identified as the ideal reaction parameters for the successful C sp C sp2 bond formation via Cu‐free coupling reaction (Table 1, entry 3).…”
Section: Resultssupporting
confidence: 88%
“…With this aim, several studies on the Pd‐catalyzed Sonogashira coupling reaction have been performed in RTILs. For instance, Mika et al reported recently a Cu‐free Pd‐catalyzed Sonogashira coupling in γ‐valerolactone‐based ionic liquids 12 . Other ionic liquids (ILs), such as [BMIM][PF 6 ], 13 [BMIM][BF 4 ], 14 and pyridine‐based ILs, 15 have also been utilized in Cu‐free Sonogashira coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…When different precursors were compared, it was revealed that using of bis(triphenylphosphine)palladium(II) dichloride (Pd(PPh 3 ) 2 Cl 2 ) and tris(dibenzylideneacetone)dipalladium(0) (Pd 2 (dba) 3 ) gave acceptable yields of 3a (Table 2, entries 1 and 5). A similar observation was reported for the Sonogashira reaction performed in biomass-originated ILs (Orha et al 2019).…”
Section: Resultssupporting
confidence: 85%
“…To demonstrate their further applicability, they were first compared to the conventional 1-butyl-3-methylimidazolium cation-based ILs in the coupling of iodobenzene (1a) and triethoxyphenylsilane (2a) as a model reaction (Scheme 1) under typically used "Hiyama conditions" using tetrabutylammonium fluoride as a F − source (Ismalaj et al 2014). As with Sonogashira coupling in ILs (Orha et al 2019), negligible conversion rates of 1a were detected in butylmethylimidazolium cation containing ILs (Table 1 entries 1-3). The reaction efficiency could be significantly increased by the introduction of tetrabutylphosphonium 4-ethoxyvalerate [TBP][4EtOV], resulting in the conversion of 1a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation